Pengaruh return on asset, debt to asset ratio dan current ratio terhadap harga saham pada perusahaan sub sektor transportasi di Bursa Efek Indonesia (BEI) Periode 2014 – 2019 - Hasanudin; DipaTaruna; Zallya Fassya (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of Return on Assets, Debt to Asset Ratio, and Current Ratio on stock prices in transportation sub-sector companies on the Indonesia Stock Exchange (IDX) for the 2014 – 2019 period. The population used in this study is transportation sub-sector companies that listed on the Indonesia Stock Exchange (IDX). The data used in this research is secondary data. The sampling technique in this study was carried out using the purposive sampling method, namely by selecting samples based on the criteria determined by the author and obtained a research sample of 12 companies during the 2014 - 2019 period. The data analysis method used in this study was descriptive analysis. , classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of this study explain that Return on Assets has a significant effect on stock prices, Debt to Asset Ratio has a significant effect on stock prices, and Current Ratio has a significant effect on stock prices.